Morfometria, germinação in vitro e ex vitro e adequação metodológica do teste de tetrazólio em sementes de Passiflora foetida var. glazziovii killip (Passifloraceae) - Costa, Poliana Rangel (2013)
The species Passiflora foetida L. has wide medical utility and ornamental, but information concerning their infraspecific taxon and the physiological potential of its seeds are still scarce. Tetrazolium tests and germination are important components for the evaluation of the physiological quality of seeds, enabling the evaluation force and deterioration. Through the application of these methodologies is possible to achieve the maximum levels of germination with getting quality seedlings. In this way, aimed to characterize P. foetida var. glaziovii Killip, evaluate their behavior in vitro and ex vitro germinal and tailor the tetrazolium test methodology. The botanical identification and characterization were performed from the observation of relevant characters as identification key. The ex vitro germination was held in roller and paper Germitest at temperatures of 25 and 20-30° C. Totally devoid of seed integument later were used in the in vitro germination tests and tetrazolium. For the in vitro germination medium was MS being the seeds put up the different qualities of light (white, red, red extreme and absence) and two temperatures (25 and 20-30° C). Tetrazolium test the seeds were submerged, tetrazolium solution at a concentration of 2.5; 5.0; 7.5 and 10 g L-1 at temperatures of 30, 35, 40 and 45° C for two hours in the absence of light. P. foetida var. glaziovii Killip is a wild species, characterized as herbaceous vine with glandular trichomes on its leaves, bracts and estipulas. This plant has small seeds of approximately 4.87 mm long and 2.15 mm wide, nonphotoblástic, and germination in vitro should be performed in alternating temperature xiii of 20-30° C. In the evaluation of force through the tetrazolium test the combination of concentration of 10 g L-1 and temperature of 30° C is recommended for this species.